Borderline Personality and the Quest for Life’s Meaning: Unraveling the Role of Interpersonal Challenges - Batool, Aqsa; Manzoor, Zeeshan; Iqbal, Hafsa (Journal of Development and Social Sciences, 2024)
This research examines the intricate connection between Borderline Personality Disorder (BPD), life’s meaning and the interpersonal difficulties related to the search for meaning, in the cultural context in Pakistan. As BPD is frequently accompanied by extreme interpersonal problems and problems with identity, it’s valuable to learn how these elements interact to influence one’s pursuit of meaning. Employing a mixed-methods design, the study included a quantitative assessment of BPD symptoms, interpersonal challenges, and meaning in life in a sample of 150 adults (75 with BPD and 75 controls) using validated scales. The qualitative component was based on semi structured interviews with 15 BPD members. Quantitative results showed significantly more interpersonal challenges in conjunction with an even more intense search for the meaning of life for those with BPD when compared with controls. BPD symptoms were positively correlated with interpersonal difficulties and negatively correlated with the presence of meaning. Cultural factors moderated the impact of interpersonal challenges on the search for meaning. Qualitative data were thematically analyzed and themes of familial expectation, societal pressure and cultural perception emerged about how these themes influenced participants’ relational struggles and existential outlooks were identified. Thus, these findings help to support the need for culturally sensitive interventions that address the interpersonal and existential dimensions of those with BPD.